Multiple squamous cell carcinomas of temporal bone years after radiotherapy for malignancy glottis-report of a rare case with review of literature - Chelakkattuparambil, Eaiby Sebastian; Ponnuvelu, Sahana; Dharman, Devi; Selvakarikalan, Selvarajesh; Veeramani, Tamilselvi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Larynx is unique in its anatomy. It is critical to map the lesions accurately so that the patient may benefit from the strategy most likely to preserve a functional larynx with the lowest likelihood of recurrence and the least morbidity. We describe a case of 60-year-old male with malignancy glottis diagnosed at the age of 43, treated with external beam radiotherapy, presented 15 years after with swelling in the right upper part of the face, lateral to the eye. Radiological investigations suggested neoplasm in the skin over the right zygomatic part of the temporal bone. Biopsy confirmed malignancy, basal cell carcinoma type. Wide local excision of the lesion with split skin grafting was done. After 2 years, he presented with right ear pain, discharge, and hard of hearing. Examination and radiological investigations confirmed a mass in the external auditory canal, infiltrating through the temporal bone. Biopsy revealed an acantholytic variant of squamous cell carcinoma (SCC). The patient was advised about treatment options and radiotherapy was chosen. Further, a literature search was conducted to detect similar cases. We describe the incidence and prevalence of radiation-induced temporal bone malignancy, an exceedingly rare and late complication of head and neck irradiation. Radiation induced SCCs are highly malignant secondary neoplasms in the head and neck region. It constitutes a therapeutic challenge because of its anatomy and the known side effects of radiation. Timely intervention with a multidisciplinary approach is necessary.